STRATEGIES AND TRAPS OF THINKING: “INTEGRANION” = INTEGRATION + UNION (RATIONAL CHOICE AND VALUE-SENSE COMPLEXES IN POST-GLOBALITY) - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2023)
The transition to post-globality as a structure and environment of social relations of the knowledge society is formed around the main directions of developing an understanding of the world around us and oneself. There is a growing awareness of the need not for "patching holes" according to the principle of "here and now", but for systemic-strategic social development and security as the determining conditions for self-realization and mutual realization. The implementation of original models of a social (people’s, socialized) state requires an expansion strategy and the corresponding sector of management, and the through value of the principles of the ecology of life – each time in forms, that are organic for the development of a particular cultural and civilizational world, therefore – innovative for the ecumene as a whole [1-5]. Along with the increasing role of the features of each of the cultural and civilizational worlds, the interpenetration of the value of the common elements of progress is also growing; new combinations of mental skills are emerging. For each of the cultural-civilizational worlds, its integration into the system of international relations, long-term and opportunistic-current alliances is not a goal, but a means of raising its security and development. That is, the use of cooperation processes (integration and unions) in solving common problems is a condition for the success of one’s modernization. Rational thinking in the development of post-global strategies requires a transition from an abstract and one-sided assessment to a concrete-universal holographic relation [6-11]. At the same time, general developed principles, approaches, discoveries are of value, and not at all the transfer of private templates and tracing paper from alien mechanisms or institutions that have grown up in a different environment. Thus, futuristic diagnostics focuses on such processes of integration and formation of alliances that would strengthen, rather than weaken, the sovereignty and specificity of each of the cultural-civilizational worlds. At the same time, "dragon’s teeth", sown by colonialism and the slave trade, play a significant role in the implementation of hyper-industrialization on a global scale as the industrial core of the new modernization. For example, the robbery of the colonies by the mother countries; the imposition of artificial state borders that do not coincide with ethno-cultural and religious ones; strengthening the problem of divided peoples, bribing and corrupting local elites; inhibition in development and so on. Vivid outbreaks of global injustice were nuclear explosions in the peaceful cities of Hiroshima and Nagasaki, the use of chemical weapons in Vietnam, the bombing of Belgrade (including bombs with depleted uranium), the destabilization of the Arab world, constant coups against progressive governments in South America, etc.